Effectiveness and safety of morinidazole in the treatment of pelvic inflammatory disease: A multicenter, prospective, open-label phase IV trial - Zhou, Ting; Yuan, Ming; Cui, Pengfei; Li, Jingjing; Jia, Feifei; Wang, Shixuan; Liu, Ronghua (Frontiers in Medicine, 2022)
Background Antimicrobial resistance to metronidazole has emerged after several decades of worldwide use of the drug. The purpose of this study was to evaluate the effectiveness, safety and population pharmacokinetics of morinidazole plus levofloxacin in adult women with pelvic inflammatory disease (PID). Methods Patients in 30 hospitals received a 14-day course of 500 mg intravenous morinidazole twice daily plus 500 mg of levofloxacin daily. A total of 474 patients were included in the safety analysis set (SS); 398 patients were included in the full analysis set (FAS); 377 patients were included in the per protocol set (PPS); 16 patients were included in the microbiologically valid (MBV) population. Results The clinical resolution rates in the FAS and PPS populations at the test of cure (TOC, primary effectiveness end point, 7–30 days post-therapy) visit were 81.91 and 82.49% (311/377), respectively. There were 332 patients who did not receive antibiotics before treatment, and the clinical cure rate was 82.83%. Among 66 patients who received antibiotics before treatment, 51 patients were clinically cured 7–30 days after treatment, with a clinical cure rate of 77.27%. The bacteriological success rate in the MBV population at the TOC visit was 87.5%. The minimum inhibitory concentration (MIC) values of morinidazole for use against these anaerobes ranged from 1 to 8 μg/mL. The rate of drug-related adverse events (AEs) was 27.43%, and no serious AEs or deaths occurred during the study. Conclusions The study showed that treatment with a 14-day course of intravenous morinidazole, 500 mg twice daily, plus levofloxacin 500 mg daily, was effective and safe. The results of this study were consistent with the results of a phase III clinical trial, which verified the effectiveness and safety of morinidazole.